2021
DOI: 10.1002/cssc.202101071
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Synthesis of High‐Molecular‐Weight Hyaluronic Acid with Immobilized Enzyme Cascades

Abstract: Industrial hyaluronic acid (HA) production comprises either fermentation with Streptococcus strains or extraction from rooster combs. The hard‐to‐control product quality is an obstacle to these processes. Enzymatic syntheses of HA were developed to produce high‐molecular‐weight HA with low dispersity. To facilitate enzyme recovery and biocatalyst re‐use, here the immobilization of cascade enzymes onto magnetic beads was used for the synthesis of uridine‐5’‐diphosphate‐α‐d‐N‐acetyl‐glucosamine (UDP‐GlcNAc), UDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…HA is a linear glycosaminoglycan (GAG) consisting of N -acetyl- d -glucosamine and d -glucuronic acid. HA derived from rooster comb [ 41 ], microbial source [ 5 ]. HA was first isolated from the vitreous humor of bovine eyes.…”
Section: Polysaccharidementioning
confidence: 99%
“…HA is a linear glycosaminoglycan (GAG) consisting of N -acetyl- d -glucosamine and d -glucuronic acid. HA derived from rooster comb [ 41 ], microbial source [ 5 ]. HA was first isolated from the vitreous humor of bovine eyes.…”
Section: Polysaccharidementioning
confidence: 99%
“…This approach is especially useful for obtaining non-natural chemicals [106] , [107] . Recent studies have shown a high efficiency of using enzyme cascades immobilized by magnetic beads for obtaining HW HA [108] . Several reviews on strategies for chemoenzymatic synthesis with an emphasis on the use of enzyme cascades have been published recently [106] , [109] .…”
Section: Ha Synthesismentioning
confidence: 99%
“…[10] Moreover, the accumulation of low length polyP and orthophosphate in the reaction mixture is not favorable, especially for repetitive batch reactions, because of their tendency to form insoluble salts with divalent metal ions. [13,14] One promising approach is the in vitro reconstitution and implementation of non-oxidative glycolysis (NOG). The NOG pathway can fully produce stoichiometric metabolites from dextrose sources to C2 metabolites, without any carbon loss.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its simple approach, PPK is typically expressed as an inclusion body [12] and its activity depends on the length of the polyP chain, which can differ greatly depending on the suppliers and their respective production methods [10] . Moreover, the accumulation of low length polyP and orthophosphate in the reaction mixture is not favorable, especially for repetitive batch reactions, because of their tendency to form insoluble salts with divalent metal ions [13,14] …”
Section: Introductionmentioning
confidence: 99%